CISSP Practice Questions Exam Cram, Fourth Edition - Gregg, Michael (Michael C.) (Pearson IT Certification, 2016)
CISSP Practice Questions Exam Cram, Fourth Edition CISSP Practice Questions Exam Cram, Fourth Edition complements any CISSP study plan with 1,038 practice test questions in the book and on the companion site - all supported by complete explanations of every answer. This package's highly realistic questions cover every area of knowledge for the new CISSP exam. Covers the critical information you'll need to know to help you pass the CISSP exam! Features 1,038 questions, organized to reflect the current CISSP exam objectives so you can easily assess your knowledge of every topic. Each question includes a detailed answer explanation. Provides complete coverage of the Common Body of Knowledge (CBK). Use our innovative Quick Check Answer Key to quickly find answers as you work your way through the questions. Companion Website Your purchase includes access to 1,038 unique practice exam questions in multiple test modes and 75 electronic flash cards. Make sure you're 100% ready for the real exam! Detailed explanations of correct and incorrect answers; Random questions and order of answers; Coverage of each current CISSP exam objective Pearson IT Certification Practice Test minimum system requirements: Windows 10, Windows 8.1, Windows 7, or Vista (SP2), Microsoft .NET Framework 4.5 Client; Pentium-class 1 GHz processor (or equivalent); 512 MB RAM; 650 MB disk space plus 50 MB for each downloaded practice exam; access to the Internet to register and download exam databases.